Connexons and pannexons: newcomers in neurophysiology - Cheung, Giselle; Chever, Oana; Rouach, Nathalie (Frontiers in Cellular Neuroscience, 2014)
Connexin hemichannels are single membrane channels which have been traditionally thought to work in pairs to form gap junction channels across two opposing cells. In astrocytes, gap junction channels allow direct intercellular communication and greatly facilitate the transmission of signals. Recently, there has been growing evidence demonstrating that connexin hemichannels, as well as pannexin channels, on their own are open in various conditions. They allow bidirectional flow of ions and signaling molecules and act as release sites for transmitters like ATP and glutamate into the extracellular space. While much attention has focused on the function of connexin hemichannels and pannexons during pathological situations like epilepsy, inflammation, neurodegeneration or ischemia, their potential roles in physiology is often ignored. In order to fully understand the dynamic properties and roles of connexin hemichannels and pannexons in the brain, it is essential to decipher whether they also have some physiological functions and contribute to normal cerebral processes. Here, we present recent studies in the CNS suggesting emerging physiological functions of connexin hemichannels and pannexons in normal neuronal activity and behavior. We also discuss how these pioneer studies pave the way for future research to extend the physiological relevance of connexons and pannexons, and some fundamental issues yet to be addressed.